TNF-alpha activates human monocytes for Paracoccidioides brasiliensis killing by an H2O2-dependent mechanism - Carmo, J. P. M.; Dias-Melicio, L. A.; Calvi, S. A.; Peracoli, M. T. S.; Soares, A. M. V. C. (Taylor & Francis Ltd, 2006)
Human monocytes activated by recombinant tumor necrosis factor alpha (TNF-alpha) exhibited significant fungicidal activity on the yeast cells of a highly virulent strain of Paracoccidioides brasiliensis. This process was significantly inhibited in the presence of catalase (CAT - a scavenger of H2O2), but not in the presence of superoxide-dismutase (SOD - a scavenger of superoxide anion) or N-G-monomethyl-L- arginine (N-G-MMLA - a nitric oxide inhibitor). Furthermore, there was a direct association between the intracellular killing of the fungus and the production of H2O2 by activated cells. These results strongly suggest a role for H2O2 in the killing of highly virulent strains of P. brasiliensis by TNF-alpha-activated human monocytes.
Keywords: P. brasiliensis; monocytes; fungicidal activity; H2O2